2005
DOI: 10.1063/1.1854723
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Ge growth at low temperature on Si(001) by ultrahigh vacuum chemical vapor deposition

Abstract: The growth of germanium at low temperature by ultrahigh vacuum chemical vapor deposition on Si(001) is investigated in real time by reflection high-energy electron diffraction. These observations are complementarily checked by atomic force microscopy, Rutherford backscattering spectrometry, transmission electron microscopy, and x-ray diffraction experiments. It can be seen that the currently observed Stranski–Krastanov-related two-dimensional (2D) to three-dimensional transition is avoided at 330 °C and that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 23 publications
4
37
0
2
Order By: Relevance
“…High-quality Ge thin films have been successfully grown on Si by a two-step UHV/CVD growth technique [16,17]. In this study, the two-step growth method was applied to grow Ge thin film by MBE instead of UHV/CVD.…”
Section: Resultsmentioning
confidence: 99%
“…High-quality Ge thin films have been successfully grown on Si by a two-step UHV/CVD growth technique [16,17]. In this study, the two-step growth method was applied to grow Ge thin film by MBE instead of UHV/CVD.…”
Section: Resultsmentioning
confidence: 99%
“…[10,13,14,18]). It is suggested that it is very difficult to fully relieve the strain in the Ge seed layer when growing at LT (300-400 1C).…”
Section: Article In Pressmentioning
confidence: 97%
“…1(c)). The temperature of 350 1C is not low enough to prohibit three-dimensional growth [18], and the surface becomes much rough. However, after deposition of HT Ge layer, the surface becomes smooth and 2 Â 1 reconstruction is rebuilt ( Fig.…”
Section: Rheed Patternsmentioning
confidence: 99%
“…The amount of defects in such heterostructures was reduced by growing Ge or close to Ge layers of GeSi at low temperatures with subsequent cycles of annealing [1,2]. Surface-active impurities (surfactants) were used to make the growing film surface planar [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%